Pengaruh Current Ratio Dan Debt To Equity Ratio Terhadap Profitabilitas ( ROE) - Yosi Tiani; Nanu Hasanuh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to prove and analyze the effect of Current Ratio and Debt to Equity Ratio to Return on Equity in basic industrial and chemical sub-sector manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2018.These are 76 companies listed on the Indonesia Stock Exchange 2016-2018. Of the 76 listed companies, 10 companies were selected using purposive sampling. The data used in this study are secondary data, with how to collect the information needed from idx in the form of financial statements for 2016-2018. The method used to analyze the relationship between independent variables with the dependent variable is multiple regression method, and assumption test. Results of the discussion shows that simultaneously the independent variables: Current Ratio and Debt to Equity Ratio with the F test, jointly affects the Return on Equity. Result partially with the t test, the variable Current Ratio and Debt to Equity Ratio have an effect against Return on Equity. Keywords : ROE, Debt to Equity Ratio, Current Ratio